Stress Response in Individuals Diagnosed with Hoarding Disorder - Hamedani, Atayeh (My University, 2014)
Hoarding disorder (HD) is characterized by (a) the acquisition of and inability to discard a large number of possessions; (b) clutter that interferes with the use of appliances and general living areas in the home; and (c) clinically significant distress or impairment in functioning. Although previous studies have reported that individuals with HD exhibit emotional dysregulation when discarding personal items, this investigation is the first to examine the biological indices of distress. The current study aimed to examine whether individuals with HD differed from healthy controls in their psychological and biological responses to a general psychosocial stressor and to investigate whether individual differences in stress response relate to differences in symptom severity and impairment. Twenty-one individuals with HD and 22 healthy controls (CTLs) completed the Trier Social Stress Task and self-reported affect and salivary cortisol responses to the stressor were assessed. Individuals with HD did not significantly differ compared to CTLs in their salivary cortisol levels in relation to the stressor. However, individuals with HD significant-ly differed compared to CTLs in their subjective levels of distress in relation to the stressor. Contrary to our hypotheses, responses to stress were not significantly correlated with measures of symptom severity and impairment due to hoarding. The current findings indicate that individuals with HD exhibit a greater self-reported emotional response to a general stressor. The implications of these findings are discussed.
Keywords: Hoarding Disorder; Stress response; Cortisol; Negative Affect; Trier social stress test